(untitled) (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to find out and describe the development of Indang Dance in the Dance Extracurricular at SMA Negeri 14 Padang. This type of research is qualitative research with a descriptive method. The research instrument is the researcher themselves, assisted with writing tools and a camera. Data was collected through literature study, observation, interviews, and documentation. The steps of data analysis are data collection, data reduction, data presentation, and drawing conclusions. The results show that the development of Indang Dance in the Dance Extracurricular at SMA Negeri 14 Padang can be seen in quality and quantity, based on planning, implementation, and performance. From the quality and quantity at the planning stage, activities are organized in a structured way with one practice session per week, designed across several practice meetings. During the implementation stage, 8 meetings were held in which the Indang dance extracurricular activities were conducted through movement practice, mastering floor patterns, dancer coordination, use of props, and adjusting to the accompanying music. Dance development focused on several elements of the dance, such as movement variations, floor patterns, costumes, accompanying music, and the dance presentation format. During the practice sessions, students showed quite a good level of enthusiasm and spirit, even though there were some obstacles, such as limited facilities and inconsistent practice schedules due to other school activities. The Indang Dance performance by the dance extracurricular participants was presented at the art performance event at SMA Negeri 14 Padang. This performance was an important moment because the Indang Dance had not been performed at school for a long time, and since 2019, the dance had almost never been showcased in school events.